Clinical and Electroencephalographic Characteristics of Juvenile Myoclonic Epilepsy in a Tertiary Care Hospital - Ahmad, Fawad; Imran Ahmad; Shafat, Saima; Liaqat, Jahanzeb; Ahmed, Naveed; Khan, Jalil (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the clinical and electroencephalographic features in juvenile myoclonic epilepsy (JME) patientsStudy Design: Prospective longitudinal study.Place and Duration of Study: Department of Neurology, Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Jul to Dec 2022.Methodology: The participants of this study were diagnosed with JME.  Patients with hypoxic brain injury, metabolic diseases, family history of progressive myoclonic epilepsy, and abnormal neurological examination or neuroimaging were excluded from study. Data was recorded from consenting patients on a pre-designed proforma recording various parameters.Results: Among 135 patients, 84 were females (62.2%) and 51 were males (37.8%). Mean age at diagnosis was 19.38±5.40 years. Positive family history was present in 22.2%. Generalized Tonic Clonic Seizures (GTCS) were most common seizure type (53.3%) at diagnosis where as GTCS + Myoclonic jerks (MJ) were most common types (68.9%) during disease course. Classic JME was present in 81.5% cases. Lack of sleep was most common precipitating factor (51.9%). Spike and polyspike slow wave activity was most common EEG abnormality in 44.5%. Majority were fit free on either valproic acid (42.2%) or levetiracetam (38.5%) whereas 20.7% had refractory seizures. Anxiety was most common associated psychiatric co-morbidity present in 14.1%. Conclusion: JME can be diagnosed by carefully eliciting history of MJ along with GTCS and finding of spike and polyspike slow wave activity in EEG. Majority achieve remission from fits either on valproic acid or levetiracetam.